First Report of Candidatus Mycoplasma haemohominis Infection in Australia Causing Persistent Fever in an Animal Carer. (1st February 2020) - Alcorn, Kylie; Gerrard, John; Cochrane, Tara; Graham, Rikki; Jennison, Amy; Irwin, Peter J; Barbosa, Amanda D
Abstract: Background: Hemotropic mycoplasmas (hemoplasmas) infect animals and humans and can lead to clinical syndromes mainly characterized by hemolytic anemia. A novel pathogen, Candidatus Mycoplasma haemohominis, was recently associated with a case of human hemoplasmosis in Europe. Here we report the first detection of this pathogen in an Australian patient exhibiting persistent fever, hemolytic anemia, and pancytopenia over a 10-month period. Methods: After exhaustive negative testing for human infectious diseases, whole genome sequencing (WGS) was performed on the patient's bone marrow aspirate, using an Illumina NextSeq500 platform. Conventional polymerase chain reaction (PCR), followed by Sanger sequencing, was then performed on blood samples using novel Mycoplasma -specific primers targeting the 16S ribosomal RNA gene. In addition, a Mycoplasma -specific fluorescence in situ hybridization (FISH) assay was developed to differentiate Mycoplasma cells from other erythrocyte inclusions (eg, Pappenheimer and Howell-Jolly bodies) which are morphologically similar to bacterial cocci by light microscopy. Results: WGS analysis revealed that approximately 0.04% of the total number of unmapped reads to human genome corresponded to Mycoplasma species. A 1-kb Mycoplasma 16S fragment was successfully amplified by conventional PCR, and sequence analyses revealed 100% identity with Candidatus Mycoplasma haemohominis. FISH confirmed that several (approximately 2%) epierythrocytic inclusions initially observed by light microscopy corresponded to Mycoplasma cells. Conclusions: This represents the second report of hemolytic anemia associated with hemoplasma infection in a human, and the first report of human hemoplasmosis in Australia. This study highlights the importance of new and emerging diagnostic approaches and need for further investigations on the epidemiology of Candidatus Mycoplasma haemohominis in Australia. Abstract : This is the first report of Candidatus Mycoplasma haemohominis in a human patient with hemolytic anemia, persistent fever, and pancytopenia in Australia. This study also describes several molecular and microscopy techniques for the detection of this pathogen in human blood.